Knowledge of breast cancer risk factors and preferred indigenous language information sources among women in lagos, Nigeria - Adesina, Evaristus; Salawu, Abiodun (International Journal of Innovative Research and Scientific Studies, 2025)
The audience's inclination towards a particular communication medium heavily influence their knowledge and attitudes towards breast cancer risk factors. Studies that have hitherto been conducted on breast cancer have mostly ignored women's awareness of risk factors and information sources in favor of prevalence rates and clinical analyses. This study investigated how information sources, including Indigenous language sources, were used for breast cancer risk factors in Lagos State. A cross-sectional survey was employed in eliciting information from 389 women randomly selected from four selected LGAs in Lagos State with the aid of a multi-staged sampling technique. Findings revealed that although internet-related platforms such as social media and websites were the predominant channels through which respondents accessed information on breast cancer risk factors, many women had little to no understanding of these risk factors. The study also found that respondents depicted a positive attitude towards breast cancer risk factors, as 72.3% were willing to conduct breast self-examinations, and 74.8% were willing to consult a medical doctor in case of a breast lump. Furthermore, findings showed that out of the six information sources examined, the internet/websites had the highest predictive value at a standardized coefficient (beta) of 0.243, followed closely by health workers regarding risk factor knowledge. Similarly, internet/websites had the most predictive value at a standardized coefficient (beta) of 0.404, followed closely by health workers at a beta value of 0.355 regarding attitude. The study highlights the need for breast cancer awareness campaigns to incorporate Indigenous language communication to improve comprehension and accessibility of breast cancer risk information. Health messages framed in Indigenous languages can enhance understanding, particularly among women with limited literacy in dominant languages. This study recommends that breast cancer awareness campaigns be initiated with messages framed positively, emphasizing risk factors and symptoms while leveraging Indigenous language communication channels to reach a broader audience effectively.